Is the private sector a good thing for the NHS?. (30th September 2014) - Smith, Richard; Peedell, Clive
Abstract : Richard Smith argues that private sector investment in new products and services is essential to maintain the NHS, but Clive Peedell believes that markets and the use of private providers in healthcare will increase costs and reduce the quality of care